TIMP-2 gene polymorphism is associated with intracerebral hemorrhage - Reuter, Björn; Bugert, Peter; Stroick, Mark Gregor; Bukow, Simone; Griebe, Martin; Hennerici, Michael G.; Fatar, Marc (Cerebrovascular diseases, 2009)
BACKGROUND: Both ischemic stroke and intracerebral hemorrhage are associated with altered expression and activation of matrix metalloproteinases (MMPs). Particularly relevant are MMP-2 and MMP-9. This proteolytic effect is dampened by tissue inhibitors of metalloproteinases (TIMPs). TIMP-2 is an important endogenous inhibitor of MMP-2. Alterations in the TIMP-2 gene expression may contribute to the incidence of ischemic stroke and intracerebral hemorrhage. - METHODS: TIMP-2 gene SNP -261G/A was genotyped from sequentially recruited stroke patients (n = 356, f/m 151/205, mean age 68.2 years, range 19-100 years) and gender and age matched controls (n = 253, f/m 114/139, mean age 68.5 years, range 32-92 years). The SNP -261G/A was detected after gene sequencing of 95 patients and controls. Furthermore, in a subgroup of 93 patients the serum levels of TIMP-2 were measured during the first 7 days after stroke onset and compared to the genotype. - RESULTS: SNP -261G/A in the TIMP-2 gene shows an allele frequency of approximately 39.14%. Homozygosity for allele A is associated significantly with the development of ICH (p = 0.025, OR = 2.020, CI = 1.115-3.661) as compared to heterozygosity and homozygosity for allele G (recessive genotypic model). Concordantly, the serum levels of TIMP-2 showed a nonsignificant decreases, depending on the genotype (p = 0.111). - CONCLUSION: We investigated a SNP 261 base pairs upstream of the start codon in exon 1 of TIMP-2. Our data suggest that carriers of homozygosity for allele A are at increased risk of developing intracerebral hemorrhage.